2021
DOI: 10.4149/neo_2021_201112n1212
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA HOTAIR regulates anoikis-resistance capacity and spheroid formation of ovarian cancer cells by recruiting EZH2 and influencing H3K27 methylation

Abstract: This study aims to investigate the role of the long non-coding RNA (lncRNA) HOX transcript antisense RNA (HOTAIR) in the regulation of anoikis resistance of ovarian cancer c ells, a prerequisite for metastasis and chemoresistance in ovarian cancer cells. Ova rian cancer SKOV3 cells were cultured in an ultra-low attachment system to establish an anoikis model. The relationship between cellular anoikis capability and HOTAIR expression level was studied by flow cytometry and RT-PCR. The ability of spheroid format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…(54). Furthermore, HOTAIR also interacts with several classic signaling pathways, which are commonly involved in oncogenesis, such as CCL22 signaling (55), the Wnt/β-catenin signaling pathway (56), EZH2 and H3K27 methylation signaling (57). All of this evidence, as well as that provided by the present meta-analysis, suggests the importance of lncRNA HOTAIR SNP in the development of lung cancer.…”
Section: A Rs920778 Controls Cases ----------------------------------...supporting
confidence: 64%
“…(54). Furthermore, HOTAIR also interacts with several classic signaling pathways, which are commonly involved in oncogenesis, such as CCL22 signaling (55), the Wnt/β-catenin signaling pathway (56), EZH2 and H3K27 methylation signaling (57). All of this evidence, as well as that provided by the present meta-analysis, suggests the importance of lncRNA HOTAIR SNP in the development of lung cancer.…”
Section: A Rs920778 Controls Cases ----------------------------------...supporting
confidence: 64%
“…As an important component of polycomb group proteins (PcGs), EZH2 has been confirmed to be overexpressed in a variety of cancer types with lethal outcomes, including OC cases [ 13 , 14 ]. The EZH2 gene mainly contributes to tumor development by promoting angiogenesis, silencing tumor suppressor genes and inhibiting the apoptosis of tumor cells [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, EZH2 is responsible for trimethylation of histone H3 on Lys27 (H3K27me3) that results in epigenetic gene silencing. Recent research indicates that EZH2 is overexpressed in various tumor tissues and closely related to tumor infiltration, metastasis and prognosis [ 13 , 14 ]. Accordingly, inhibition of EZH2 might be a promising strategy for therapies of cancers in the future.…”
Section: Introductionmentioning
confidence: 99%
“…However, the researches focused on the speci c function of ASH1L-AS1 in the progression of OC are rare, which aroused our great interest in exploring something deeper in this topic. Moreover, enhancer of zester homolog 2 (EZH2) is well-known as a histone methyl transferase could regulate polycomb repressive complex 2 (PRC2) to mediate the trimethylating the lysine 27 residue of histone H3 (H3K27me3), the overexpression of which has been implicated in the tumor growth and chemoresistance in OC [13,14]. A previous study demonstrated that the methylation of cannabinoid receptor interacting protein 1 (CNRIP1) promoter is involved in the regulation of the activity for cancerous cells [15,16], which was identi ed as a downstream gene of ASH1L-AS1 in our earlier investigation using bioinformatic analysis.…”
Section: Introductionmentioning
confidence: 99%